Preparation, Characterization of Carboxyl Polyaldehyde Sugars and Application as Innovative Anti-crease Finishing Agents for Cotton Fabric. Issue 15 (23rd November 2022) - Lou, Jiangfei; Wang, Dan; Fan, Xuerong
ABSTRACT: We have designed and prepared four new cellulose cross-linking agents using NaClO/NaBr/TEMPO and sodium periodate selective catalytic oxidation systems. First, the primary hydroxyl group of sucrose, trehalose, maltose, or lactose was carboxylated through NaClO/NaBr/TEMPO system, and then sodium periodate was used to selectively oxidize the carboxyl compound to obtain carboxyl polyaldehyde sugars. They contained multiple aldehyde groups and carboxyl groups in the molecule, had high reactivity, and can be covalently cross-linked with cellulose. To evaluate crosslinking ability, carboxyl polyaldehyde sugars were applied to the anti-crease finishing of cotton fabrics. The treated cotton fabric had superior anti-crease and hydrophilicity properties, and the crease recovery angle reached more than 260°, wetting time was less than 5 s. Possible crosslinking mechanisms of etherification and esterification under different catalysts and curing temperatures have been studied.